'n Kijk op kunst. - Van den broeck, L.; Debersaques, S.; Geivers, R.; Van Haesebrouck, M.; Geerinckx, L. (Antwerpen : Standaard Educatieve Uitgeverij, 1988)
Aalto, Alvar ; Albers, Josef ; Appel, Karel ; Archipenko, Alexander ; Arp, Hans (Jean) ; van den Berghe, Frits ; Boccioni, Umberto ; Brancusi, Constantin ; Braque, Georges ; Breuer, Marcel ; Burri, Alberto ; Calder, Alexander ; Carrà, C. ; César ; De Chirico, Giorgio ; Christo ; Dali, Salvador ; Deknock, P. ; Delaunay, Robert ; Dotremont, Christian ; Dubuffet, Jean ; Duchamp, Marcel ; Duchamp-Villon, Raymond ; Epstein, Jacob ; Escher, Maurits Cornelis ; Estes, Richard ; Fadi, M. ; Gabo, Naum ; Giacometti, Alberto ; Goldberg, B. ; Gris, Juan ; Hamilton, Richard ; Harsay, H. ; Heckel, Erich ; Jacobsen, A. ; Kandinsky, Wassily ; Kelly, Ellsworth ; Kirchner, Ernst Ludwig ; Klee, Paul ; de Kooning, Willem ; Kosuth, Joseph ; Larionov, Michail ; Le Corbusier ; Leger, Fernand ; Lichtenstein, Roy ; Lucebert ; Mackintosh, Charles Rennie ; Magritte, René ; Maillol, Aristide ; Malevich, Kasimir ; Marc, Franz ; Marcase ; Mathieu, Georges ; Merz, Mario ; Minne, George ; Miro, Joan ; Modigliani, Amedeo ; Moholy-Nagy, Laszlo ; Mondriaan, Piet ; Moore, Henry ; Niemeyer, O. ; Noland, Kenneth ; van Ostaijen, Paul ; Pauwels, A. ; Permeke, Constant ; Perriaud, C. ; Piano, Renzo ; Picasso, Pablo ; Pollock, Jackson ; Ponti, Gio ; Rauschenberg, Robert ; Raveel, Roger ; Raysse, Martial ; Richier, Germaine ; Riley, Bridget ; Rogers, Richard ; Rosenquist, James ; Rothko, Mark ; Rouault, Georges ; Rousseau, Henri ; Saarinen, E. ; Schmidt-Rottluff, Karl ; De Smet, Gust ; Smithson, Robert ; Sottsass, Ettore ; Starck, Philippe ; Stella, Frank ; Thonet, Michael ; Tzara, Tristan ; Vasarely, Victor ; de Velde, Henri Van ; Warhol, Andy ; Wouters, Rik ; Wright, Frank Lloyd ; Zadkine, Ossip
boek